Konsumsi Buah Kurma Meningkatkan Kadar Hemoglobin pada Remaja Putri - M. Ridwan; Sri Lestariningsih; Gangsar Indah Lestari (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2018)
Background: The prevalence of anemia in adult women aged 15-19 years in Metro City in 2016 was 67%, higher than the national rate of 35.3%. Purpose: The purpose of this study is to determine the effect of dates on the increase in hemoglobin (Hb) levels in Madrasah Aliyah students in Metro City. Methods: This study was a pre-experimental research design of the one group pretest - posttest. The study population was a class XI Madrasah Aliyah student in Metro city who experienced anemia with a sample of 71 students. The variables analyzed were the average Hb before and after the intervention by giving dates for 7 days. Univariate analysis using mean, median and bivariate analysis using non parametric dependent t test (Wilcoxon test). Results: The results of the study average Hb levels before the intervention were 10.45 gr / dL (46.5%) and after the intervention 11.70 gr / dL (49.3%), while the average increase in Hb levels after the intervention 1 , 1 gr / dL. Statistical test results obtained p value = 0,000, meaning that there is an influence of dates on increasing Hb levels. Conclusion: Consumption of dates for seven days increases the Hb level of 1.1 gr / dL. Prevention of anemia in young women during menstruation can consume dates as a complementary therapy that is still natural.